THE ANALYSIS OF IMPLEMENTATION ACTIVITY BASED COSTING TO DETERMINING THE COST OF PRODUCTION ASSESSED IN ISLAMIC PERSPECTIVES AT PT. REKATANI DHARMA JAYA, SUMBERGEMPOL - Tika Maulina (State Islamic Institute (IAIN) Tulungagung, 2021)
The research background interested that calculation of cost price production conducted by PT. Rekatani Dharma Jaya still use Traditional System. In the islamic factory also must be based on islamic to note down the financial transaction and also a honesty, so factory's worker did that conflicting of islamic law. `In this research used to quantitative approach with descriptive research. The data resource got that were secondary and premiere data. The collecting data in this research were documentation and observation. The analysis data whereas used suitable formulation by Activity Based Costing method. The result of this research are : (1) The calculation of cost price per unit production petroganic menure by traditional system as wide as 612,47, (2) The results calculation cost price petraganic menure used to Activity Based Costing 806,53, (3) The result analysis indicated that Activity Based Costing if compare the traditional method the result provides that larger with difference +194,06. (4) Activity Based Costing can applied on PT. Rekatani Dharma Jaya factory by a product, (5) The Activity Based Costing application to observe of Islamic Perspective to indicates that PT. Rekatani Dharma Jaya was conducted Activity Based Costing based on islamic perspective well.